A history of conflict between the Nyaribari and Kitutu sub- clans at Keroka in Nyamira and Kisii Counties, Kenya, 1820 - 2017 - Moturi, Samuel Benn (Jooust, 2023)
A lot of research has been done on conflict and disputes between communities, nations, and organized groups across the globe. Little, however, has been done on conflicts involving smaller groups within larger communities. The overall image that emerges, therefore, is that conflicts and disputes only occur between communities, nations, and specially organized groups, a situation which is not fully correct, as far as the occurrence of conflict is concerned. This study looked at a unique situation of conflict between Nyaribari and Kitutu who share same origin, history and cultural values yet have been engaged in conflict since the 19th century. Specific objectives were to: trace the history of the Sweta Clan and the relationship between Nyaribari and Kitutu sub-clans, assess the extent and nature of inter-clan conflicts among the Nyaribari and Kitutu clans in Keroka township; examine the socio-economic environment influencing inter-clan conflicts among the Nyaribari and Kitutu clans in Keroka township and discuss the management strategies employed in the inter clan conflict between Nyaribari and Kitutu. The study was based on two theories which are Social Conflict Theory by Karl Max (1818-1883). Using descriptive survey design whereby both quantitative and qualitative approaches the study gained a deeper insight into the problem under investigation. Data was obtained from the 100 respondents selected through purposive and snowballing sampling techniques. This consisted of 25 Key Informant Interviews, 60 oral interviews and 15 participants in 2 Focus Group Discussions. Two of the FGD’s were for the different clan elders from Nyamira and Kisii while 1 FGD was for urban dwellers in Keroka. The FGD’s for county officials helped the research to address the bias of the respondents from the two sub-clans on which the study focused on. Verbatim narratives were used in presenting qualitative data. The secondary data method was collected from various documents whether published or non-published. These included journal articles, books, previous master oral thesis, doctoral thesis and data from government offices with a view of obtaining related literature on the subject under study. Thematic techniques were employed in analyzing qualitative data. The study findings have both policy and academic implications to the communities, local leaders and the National and County governments in addressing inter-clan conflicts between communities living in Kisii and Nyamira counties. The findings of the study indicate that conflict between Nyaribari and Kitutu clans started earlier during their dispersal and settlement in the Gusii highlands. The recurrence of the inter clan conflicts in Keroka is associated to competition for the scarce resources as well as political motivations. The study recommends that the government, and all other stakeholders, should be aware of the existence of clan conflicts as they have the potential of affecting socio-economic and political development just as inter-ethnic conflicts. Also, there is need for public education so that communities make use of historical facts and events positively.
Keywords: Historical of conflicts between sub- clans, Kenya.; Conflicts between the Nyaribari and Kitutu sub- clans, Kenya